Control of Tandem-Type Two-Wheel Vehicle at Various Notion Models Along Spatial Curved Lay of Line - Beshta, А. S.; Kravets, Viktor V.; Bas, Kostyantyn M.; Kravets, Tamila V.; Tokar, Larisa A. (Національний гірничий університет, 2015)
EN: Wheeled vehicle is considered as a material point under the conditions of non-uniform movement along curved spatial lay of line. Hodograph in a class of spatial lines describes kinematics of a vehicle. A kinetostatics problem of tandem-type two-wheel vehicle is being solved. Equivalent contact dynamics are being determined.

UK: Двоколісний екіпаж розглядається як матеріальна точка при нерівномірному русі по просторовій криволінійній трасі. Кінематика екіпажу представлена через годограф в класі спірале-гвинтових ліній. Розв’язується задача кінетостатики двоколісного екіпажу тандемної схеми, визначаються еквівалентні контактні рушійні сили.

RU: Двухколёсный экипаж рассматривается как материальная точка при неравномерном движении по пространственной криволинейной трассе. Кинематика экипажа описывается годографом в классе спиралевинтовых линий. Решается задача кинетостатики двухколёсного екипажа тандемной схемы, определяются еквивалентные контактные движущие силы.
Керованість двоколісного екіпажу тандемної схеми при різних режимах руху по просторовій криволінійній трасі
Управляемость двухколёсного екипажа тандемной схемы при различних режимах движения по пространственной криволинейной трассе
Keywords: hodograph; kinematics; kinetostatics; Euler-Lagrange equations; equivalent contact dynamics; static invariants; годограф; кінематика; кінетостатика; рівняння Ейлера-Лагранжа; еквівалентні сили; статичні інваріанти; кинематика; кинетостатика; уравнения Ейлера-Лагранжа; еквивалентные силы; статические инварианты; КТМЕХ